Regulasi Diri Dengan Perilaku Cyberloafing Pada Karyawan - Vira Ayu Putri Hadiansah; Diah Sofiah; Hikmah Husniyah Farhanindya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Cyberloafing is a behavior where employees use internet access during working hours for personal interests, which can potentially reduce productivity. This study aims to determine the relationship between self-regulation and cyberloafing behavior among employees. This research uses a quantitative method with a correlation design. The subjects of this study were 100 employees of PT. Total Retalindo Maju Bersama. Data collection used a self-regulation scale and a cyberloafing scale. The data analysis technique used was Pearson Product Moment correlation. The results showed a correlation coefficient (r) of -0.315 with a significance level of 0.001 (p 0.05). This indicates that there is a significant negative relationship between self-regulation and cyberloafing. The contribution of self-regulation to cyberloafing is 9.9%, while the rest is influenced by other factors.